(untitled) (Anclajes, 2021)
Studies about the relationship between language in society emerged in the mid-20th century, and reached a peak at the end of the century with analyses on language ideologies and the most recent developments in glotopolitics and linguistic historiography. Both perspectives share a common framework: that language in modernity is a discursive artifact whose history and social construction is eminently political. The contributions of these theoretical-critical perspectives are reviewed and related to some research published in the journal Anclajes.